2005
DOI: 10.3349/ymj.2005.46.3.399
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Rifaximin and Lactulose for the Treatment of Hepatic Encephalopathy: A Prospective Randomized Study

Abstract: Rifaximin has been reported to be effective for the treatment of hepatic encephalopathy (HE) in Europe. However, it is unknown whether Rifaximin is effective for the treatment of HE in Koreans, therefore we conducted a open-label prospective randomized study to evaluate the efficacy of rifaximin versus lactulose in Korean patients. Fifty-four patients with liver cirrhosis and hepatic encephalopathy were enrolled. Thirty-two patients were randomized to receive rifaximin and 22 to receive lactulose both over a 7… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
113
3
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 115 publications
(120 citation statements)
references
References 31 publications
3
113
3
1
Order By: Relevance
“…There was significant difference of mean of PSE index in both groups. This result differ with other study conducted by Paik et al 31 where PSE index were similarly decreased in both group (p = <0.001).…”
Section: Discussioncontrasting
confidence: 57%
See 3 more Smart Citations
“…There was significant difference of mean of PSE index in both groups. This result differ with other study conducted by Paik et al 31 where PSE index were similarly decreased in both group (p = <0.001).…”
Section: Discussioncontrasting
confidence: 57%
“…But, this result differ with other study conducted by Paik et al showed the mean HE grade was similarly decreased within the study group (p=<0.001). 31 At the end of treatment, the mean PSE index was also more decreased in group A (11.71'!3.35, p = <0.05) than in group B (11.76'!6.10, p = <0.05). There was significant difference of mean of PSE index in both groups.…”
Section: Discussionmentioning
confidence: 84%
See 2 more Smart Citations
“…The side effects of non-absorbable disaccharides include abdominal pain, flatulence, and severe diarrhoea, which may lead to the cessation of therapy. 8 A few patients dislike the sweet taste of the preparations, so dilution with water or administering the preparation with fruit juice can mask the taste. 9,10,11 Rifaximin is a semi-synthetic, gut-selective, and nonabsorbable oral antibiotic, derived from rifamycin and a structural analogue of rifampin.…”
mentioning
confidence: 99%